A Rhodium(II)‐Catalyzed Formal [4+1]‐Cycloaddition toward Spirooxindole Pyrrolone Construction Employing Vinyl Isocyanates as 1, 4‐Dipoles. (3rd May 2017) - Meloche, Jennifer L.; Ashfeld, Brandon L.
Abstract: A Rh II ‐catalyzed, formal [4+1]‐cycloaddition between diazooxindoles as electrophilic C1 synthons and 1, 3‐heterodienes for the construction of spirooxindole pyrrolones is described. Employing vinyl isocyanates as 1, 4‐dipoles, the cycloannulation occurs under relatively mild conditions and provides the corresponding pyrrolones in good to excellent yields.